2015
DOI: 10.1007/s11056-015-9478-4
|View full text |Cite
|
Sign up to set email alerts
|

A new device to foster oak forest restoration via seed sowing

Abstract: Seed sowing may be a cheap and efficient reforestation method that can yield high-quality seedlings for many woody species, but this option is usually discarded against seedling planting due to the high seed losses to mammal predators. The search for methods to reduce seed predation is therefore a key issue to broaden reforestation options and restoration success. In this study we tested (1) the effectiveness of a new device to prevent small mammals from consuming large seeds such as acorns and (2) its effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…Other studies, however, have documented the spatial patterns and effects of long-distance oak dispersal at the landscape scale and hence the importance of isolated oaks as seed sources (Gómez 2003;Purves et al 2007). Acorn physical protection against predators is needed in Mediterranean environments to ensure oak establishment after seeding (Adams et al 1992;Castro et al 2015), as other methods such as chemical repellents have been shown to be unsuccessful (Leverkus et al 2013).…”
mentioning
confidence: 99%
“…Other studies, however, have documented the spatial patterns and effects of long-distance oak dispersal at the landscape scale and hence the importance of isolated oaks as seed sources (Gómez 2003;Purves et al 2007). Acorn physical protection against predators is needed in Mediterranean environments to ensure oak establishment after seeding (Adams et al 1992;Castro et al 2015), as other methods such as chemical repellents have been shown to be unsuccessful (Leverkus et al 2013).…”
mentioning
confidence: 99%
“…Thus, rather than deterring mammal predators, it is possible that diesel attracted them, which is in opposition with the study upon which we based our hypotheses [20]. This effect-or lack of an effect-of diesel, however, could vary with the identity of acorn predators, as do several other acorn-protector methods [2,8,19,23]. Instead, our results show that the lack of a reduction in acorn predation by diesel application was consistent across the two levels of acorn predators (Figure 1; diesel × exclosure interaction: χ 2 = 0.91, p = 0.34).…”
Section: Acorn Predationmentioning
confidence: 91%
“…Previous studies have documented high rates of acorn predation in this area, both by rodents and wild boars [21][22][23]. We used two fenced plots of ca.…”
Section: Acorn Predation Experimentsmentioning
confidence: 99%
See 2 more Smart Citations